Alterations of Regional Homogeneity and Functional Connectivity Following Short-Term Mindfulness Meditation in Healthy Volunteers - Xiao, Qin; Zhao, Xingrong; Bi, Guoli; Wu, Lisha; Zhang, Hongjiang; Liu, Ruixiang; Zhong, Jingmei; Wu, Shaoyuan; Zeng, Yong; Cui, Liqian; Chen, Yanmei; Wu, Kunhua; et al. (Frontiers in Human Neuroscience, 2019)
Mindfulness is described as the nonjudgmental awareness of experiences in the present moment. The sustained practice of mindfulness may also have beneficial effects on an individual’s well-being. For instance, mindfulness meditation is an effective approach for improving emotion regulation. Specifically, the early stage of mindfulness meditation training enhances emotional monitoring systems related to attention regulation and executive function. Default mode network (DMN) could probably be observed of reduced involvement corresponding to attenuated mind wandering. In the present study, we hypothesized that alterations of functional activity in the frontal-parietal cortex and DMN may be induced by short-term mindfulness meditation. In this study, before and after 8 weeks of weekly Mindfulness-Based Stress Reduction (MBSR) training, healthy participants were evaluated using a mindfulness questionnaire and an affect schedule, as well as via resting-state functional magnetic resonance imaging. Sixteen right-handed non-meditators were enrolled. Another 16 demographically matched healthy adults without any meditation experience were recruited as controls. Pre- and post-MBSR assessments were compared. Increased regional homogeneity in the right superior parietal lobule and left postcentral gyrus (PoCG), as well as altered functional connectivity in PoCG-related networks, were observed post-MBSR. The mindfulness questionnaire scores also improved and negative affect was significantly decreased after MBSR. Together with reduced involvement of the posterior brain, our results suggest a tendency toward stronger involvement of the parietal cortex in mindfulness beginners. This study provides novel evidence regarding the optimization of emotional processing with short-term mindfulness meditation.